Gastrointestinal neoplasia in patients with inflammatory bowel disease: Opportunities to enhance preventative strategies. Issue 6 (14th May 2019) - Young, Edward; Lawrence, Matthew; Thomas, Michelle; Andrews, Jane
Abstract : Background and Aims: Gastrointestinal (GI) adenocarcinoma, especially colorectal cancer (CRC), is a devastating complication of inflammatory bowel disease (IBD). We sought to examine the role of chronic inflammation and other possible predictors of the development of CRC, as well as assess as yet unexamined factors such as psychological comorbidity and engagement in care. Methods: This study included all patients involved in a tertiary hospital IBD service diagnosed with CRC between 2007 and 2017. Reports from histological specimens were assessed, and all those with adenocarcinoma, high‐grade dysplasia (HGD), or multifocal low‐grade dysplasia (LGD) originating within IBD‐affected mucosa were included in the study. Results: A total of 32 patients were included in the study (17 with adenocarcinoma and 15 with HGD/multifocal LGD). The majority had a duration of disease >20 years. Eleven patients (34%, CI 20–52%) had previous disease‐related surgery, and 16 (50%, CI 34–66%) had multiple previous disease‐related admissions. Thirteen patients (62%, CI 41–79%) had >50% of CRP results higher than 8 mg/L. Psychiatric comorbidities were common, with 19 patients (59%, CI 42–74%) having a psychiatric comorbidity or poor engagement in treatment. Conclusion: In this cohort, we have highlighted poor engagement, hesitation to up‐titrate therapy when indicated, and psychological comorbidities as likely contributors to poor disease control and development of GI adenocarcinoma. Based on our data, these easily identifiable clinical care factors should not be overlooked when addressing IBD‐related GI malignancy prevention. Additional research is required to assess a direct causal relationship, but this study would support the incorporation of psychology services into IBD clinics. Abstract : Gastrointestinal adenocarcinoma, especially colorectal cancer (CRC), is a devastating complication of inflammatory bowel disease (IBD). This study highlights poor engagement, hesitation to up‐titrate therapy when indicated, and psychological comorbidities as new risk factors of which clinicians should be aware.